(untitled) (Research, Society and Development, 2021)
Knowing the epidemiology of land transport accidents is essential to propose actions for the prevention of this incident aimed at the most vulnerable public. Thus, the objective of this article was to describe and identify the victims of this condition served by the Emergency Mobile Care Service in Dourados, Mato Grosso do Sul. The study was based on the analysis of the attendance records carried out by SAMU from June 1, 2018 to May 30, 2019. Traffic accidents represented 52.77% of the total attendances SAMU, most of which were attended by the basic support unit. The sex most affected was male and the most prevalent age group was 20 to 39 years old with 53.39% of the total victims. The most prevalent accident was the collision between motor vehicles, with Sunday being the day of the week with the highest risk and the time with the highest record of incidents was from 18:00 to 23:59. Of the total accidents studied, 12 resulted in deaths, with the highest percentage of deceased males (91.66%). In this way, SAMU service forms are a valuable source of information for health surveillance and demonstrate their ability to contribute to the monitoring of these diseases and to point out the risk factors associated with care in the municipality.